2011
DOI: 10.1007/s10103-011-0930-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low-level laser irradiation on differentiation and proliferation of human bone marrow mesenchymal stem cells into neurons and osteoblasts—an in vitro study

Abstract: Bone marrow-derived mesenchymal stem cells (BMSCs) are promising for use in regenerative medicine. Several studies have shown that low-level laser irradiation (LLLI) could affect the differentiation and proliferation of MSCs. The aim of this study was to examine the influence of LLLI at different energy densities on BMSCs differentiation into neuron and osteoblast. Human BMSCs were cultured and induced to differentiate to either neuron or osteoblast in the absence or presence of LLLI. Gallium aluminum arsenide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
85
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 22 publications
12
85
2
4
Order By: Relevance
“…LLLT has been shown to have various biostimulatory effects, such as increase cell proliferation and accelerate tissue metabolism [12,21,22]. In this context, several studies demonstrated that LLLT had a positive effect in the process of bone consolidation in experimental models in rats [9,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…LLLT has been shown to have various biostimulatory effects, such as increase cell proliferation and accelerate tissue metabolism [12,21,22]. In this context, several studies demonstrated that LLLT had a positive effect in the process of bone consolidation in experimental models in rats [9,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…It might be tempting to postulate that this population consists of neurons derived from phenotypically modified mBMCs. Such transformation has been reported in vitro, 21,22 but new experiments will be required to answer this question in our in vivo model. In similarly lesioned and transplanted animals, we were able to show that transplanted cells apparently survive for a long time.…”
Section: Discussionmentioning
confidence: 67%
“…28 The object recognition paradigms have been reported to be affected by striatal lesions in rats. 21 Our results show that QA striatal lesion reduces the exploring behavior and the identification of the novel object in the object recognition test. Transplanted animals explore significantly more and show a preference for the exploration of the novel object, suggesting a recovery of memory and visual recognition; however, the question of whether this is the result of the presence of replacement cells or an unspecific effect of injection emerges after the improvement shown by DMEM-treated animals in this test.…”
mentioning
confidence: 58%
“…Some studies focused on osteoblastic differentiation using LLLT. The results of three studies showed that LLLT was effective in the stimulation of osteoblasts differentiation [31][32][33]. On the other hand Bouvet-Gerbettaz et al [34] and Coombe et al [35] showed no beneficial effect of laser on the proliferation and differentiation of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%